Growth, carcass characteristics, meat quality, blood indices and gut microbiota of broiler chickens fed diets enriched with a combination of organic Zn, Se and Si nanoparticles - Elwy A. Ashour; Ahmed K. Aldhalmi; Mahmoud Kamal; Azza R.F. El dosokey; Ayman A. Swelum (Journal of Applied Poultry Research)
Summary: This research studied the impacts of feeding different amounts of ZnNPs, SeNPs, and SiNPs on the carcass, gut microbiota, meat quality, growth performance, and blood markers in broilers up to 38 days old. For a total of 300 chicks, five groups were given six replications of ten unsexed one-week broiler chicks (Cobb). At various doses, the five experimental treatment groups received corn-soybean meal-based nutritional supplements: 0.0, 1.5 mg/kg SeNPs + 2.0 mg/kg ZnNPs, 1.5 mg/kg SeNPs + 3.0 mg/kg SiNPs, 2.0 mg/kg ZnNPs + 3.0 mg/kg SiNPs, and 1.5 mg/kg SeNPs + 2.0 mg/kg ZnNPs + 3.0 mg/kg SiNPs. The results showed significant differences (P≤0.05) between the treatments in the period from 22–38 days and 7–38 days. We observed that the birds in T2 consumed the most FI, while those in T3 and T4 consumed the least. The T4 group had a higher FCR than the other groups, but BWG and PI did not differ. The findings indicated no significant variations (P≤0.05) in carcass characteristics among the treatments. The outcomes found that administering SeNPs, ZnNPs, and SiNPs to birds significantly reduced their LDL, belly fat, and cholesterol. It also significantly impacted their T3, T4, IgA, and IgG levels and increased their HDL levels. In conclusion, SeNPs, ZnNPs, and SiNPs improved broiler performance, certain carcass features, gut microbial load, and improved meat quality for end consumers.